TARAS SHEVCHENKO AND MYKHAYLO DRAHOMANOV: AT THE CROSSROADS OF IDEOLOGIES - Pikhmanets’, R. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article traces formation of Shevchenko scientific studies in the second half of the XIXth century. Mykhaylo Drahomanov made the first steps in this direction. But due to personal-ideological superstitions and ideological prejudices his efforts were wasteful. As a result, there was created a special matrix of that approach, founded on political or class principles and cliches – with inevitable misinterpretations and insinuations.